Ham Radio: An Introduction to the World Beyond cb - Kuslan, Richard David; Kuslan, Louis I. (Prentice-Hall, 1981)
Discusses setting up and operating a ham radio station, including obtaining the necessary equipment and operator's license.
Keywords: Amateur radio stations; Juvenile literature; dept.nhstc; faculty_collection